Gambaran Pengetahuan Sikap dan Perilaku Tentang Bullying pada Remaja di Sma Negeri 5 Surakarta - Melsiana Rhebi (Lembaga Pengembangan Kinerja Dosen, 2024)
Bullying is defined as the behavior of stalking someone through attitudes, actions or words. Bullying cases are often found to occur among school children who are often not aware of it due to a lack of good knowledge about what bullying is, the forms and impacts of bullying. The high level of students' knowledge about bullying has an impact on students' positive behavior and attitudes which will avoid bullying activities. The aim of this research is to determine the description of knowledge, attitudes and behavior regarding bullying among teenagers at Senior High School 5 Surakarta. This research method uses quantitative with a quantitative descriptive design. Sampling in this study used a purposive sampling technique with a total of 92 respondents. The results of the analysis show that the description of knowledge about bullying among teenagers at Senior High School 5 Surakarta is mostly in the good category (16- 20) 76 - 100%, namely 89 respondents (96.7%), attitudes about bullying among teenagers at Senior High School 5 Surakarta most were in the very good category (21-25) 76-100%, namely 91 respondents (98.9%), and behavior regarding bullying in teenagers at Senior High School 5 Surakarta was mostly in the healthy category (1-12), namely 87 respondents (94.6%), so it is hoped that from the results of this research schools will further develop anti-bullying programs and involve all school parties in handling bullying behavior and schools will be able to provide education in the form of poster media once a month to students about the negative impacts of bullying and how to report it if they are victims or witnesses of bullying.